Application of Critical Race Theory to knowledge organization and representation - Martinez-Avila, Daniel [UNESP]; Ferreira, Marcio [UNESP]; Magro, Jose L. (Univ Zaragoza, 2015)
In this paper we introduce the characteristics and methodological possibilities of applying the Critical Race Theory to knowledge organization and representation, and more specifically to the bibliographic classifications that are used in Brazil. We identify these classifications as institutions and outline the main points of a project of replacement of any instances of racism by anti-racist alternatives.
Keywords: Critical Race Theory; Bibliographic classifications; Methodology; Knowledge organization; Ethical aspects